THE LIBERATION OF WOMEN AND THE EDUCATIONAL SYSTEM - Feldhammer, Louis (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1970)
Any discussion of the relationship between women and the educational system must begin by dispelling the tremendous edifice of erroneous beliefs regarding women in contemporary society. The mythology surrounding the socially normative definitions of women is enough to make any professional anthropologist think he has arrived in a society fraught with a peculiar tendency toward superstition and irrational mysticism. Of course, it should be clearly understood that social norms are not wantonly irrational but invariably serve clearly-defined purposes. As we shall see, the dominant ideology surrounding women functions to maintain a status-quo beneficial to those small social groups - invariably male-dominated - possessing a disproporlionate amount of the economic and, hence, political power.